Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Repeating for the sake of TeX rendering:

Does the functional equation $f(1/r) = rf(r)$ have any nontrivial solutions besides $f(r) = 1/\sqrt{r}$?

share|improve this question
    
The titles of the posts are also TeX-rendered. –  Adrian Petrescu Mar 24 '11 at 2:47

3 Answers 3

up vote 15 down vote accepted

There are a huge number of solutions. Let $g$ be any function from $(-1,1]$ to $\mathbb{R}$. Define a function $f: \mathbb{R} \to \mathbb{R}$ by $f(x)=g(x)$ if $x \in (-1,1]$, $f(-1)=0$, and $f(x)=(1/x)g(1/x)$ otherwise. Then $f$ satisfies your equation.

share|improve this answer

Yes. If you want another function defined on $\mathbb{R}^+$: Suppose you have a function $g$ which is invariant under inversion $g(1/z)=g(z)$, then $f(z)\cdot g(z)$ is a new function satisfying your functional equation. (f is your function $z\mapsto 1/\sqrt{z}$) For $g$ you can for example take $z\mapsto ln(z)^2$.

EDIT: I just wanted to add a "full solution" to this problem. Suppose you have a function f on $\mathbb{R}^+$ which satisfies your functional equation: Define $g(r) = \frac{1}{2}\sqrt{r}f(r)$, which is invariant under inversion and we have $f(r)=\frac{2}{\sqrt{r}}\cdot g(r)=\frac{1}{\sqrt{r}}\cdot(g(r)+g(\frac{1}{r}))$.

Conversely for any function g on $\mathbb{R}^+$ we have that $f=\frac{1}{\sqrt{r}}\cdot(g(r)+g(\frac{1}{r}))$ satisfies your functional equation.

So the set of solutions to your equation is $\{\frac{1}{\sqrt{r}}\cdot(g(r)+g(\frac{1}{r}))\}$, where g runs through all the functions on $\mathbb{R}^+$.

share|improve this answer

Jacobi's theta function, which is intimately related to the Riemann zeta function, is a very famous solution of your functional equation.

The functional equation is related to symmetry properties of the Mellin transform:

For $x>0,$ given the Mellin transform for $0<real(s)<1$

$$\hat{f}(s)=\int_{0}^{\infty }x^{s-1}f(x)\,dx,$$ then

$$f(x)=\frac{1}{x}f(\frac{1}{x})\text{ iff } \hat{f}(s)=\hat{f}(1-s).$$

(Two changes of variables show this: $x$ to $1/x$ and $s$ to $1-s$.)

Riemann's $\xi(s)$ function satisfies, for $0<real(s)<1$,

$$\xi(s)=\xi(1-s) = \pi^{-s/2}\ \Gamma\left(\frac{s}{2}\right)\ \zeta(s)=\int_{0}^{\infty }[\vartheta (0;ix^2)-(1+\frac{1}{x})]x^{s-1}\,dx.$$

where $\vartheta (z;\tau)$ is Jacobi's theta function.

By the Mellin transform theorem then

$$\psi(x)=\vartheta (0;ix^2)-(1+\frac{1}{x})=\frac{1}{x}\psi(\frac{1}{x})$$

and since $$g(x)=1+\frac{1}{x}=\frac{1}{x}g(\frac{1}{x}),$$ then

$$\vartheta (0;ix^2)=\frac{1}{x}\vartheta (0;\frac{i}{x^{2}}).$$

Note: As a series expression

$$\psi(x)=\frac{-1}{x}+2\sum_{n=1}^{\infty}exp(-\pi n^{2}x^2),$$

and for $0<real(s)<1$

$$\xi(s)=\lim_{L\to +\infty, a\to 0^+}\frac{L^{s-1}}{s-1}+\frac{-a^{s}}{s}+\int_{a}^{L }[\vartheta (0;ix^2)-(1+\frac{1}{x})]x^{s-1}\,dx.$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.